Analysis of quantitative and qualitative features of the intervertebral discs of the cervical part of the vertebral column in individuals of the juvenile age of both sexes. - Adamovych, O. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. In recent years vertebral pathology occupy one of the leading places among the diseases that cause temporal disability. Therefore, the current problem is to search for diagnostic methods that would detect signs of pathology at the pre-clinical stages and designing criteria for early diagnosis. For this reason a deep and thorough studies of the structures of the vertebral column in normal condition considering age, sex, constitutional and individual characteristics are needed. Objective. The aim of our study was to clarify the characteristics of morphometric parameters and density of the intervertebral discs of the cervical part of vertebral column in people of the juvenile age of different sexes. Methods. In the process of work we have processed 39 CT scans of individuals of the juvenile age (18-21 years), including - 18 women and 21 men who underwent computer tomography (CT) examination or examination on pathologies not related to the state of the vertebral column, bone and cartilage tissue, or diseases that could influence on it. A survey performed on computer tomograph of the fourth generation TSX-101A Aquilion 16. During the study it was measured height and density of the intervertebral discs of the cervical vertebrae. For the measurement a standard computer program K-Pacs-Lite was used. Linear dimensions measured in millimeters (mm), density - Haunsfilda units (UH). Results. It was determined that in the lateral projection the first intervertebral disc of the cervical vertebrae has the lowest height in the center, all the other disks have the greatest height in the center; the height on the anterior edge is higher than on the posterior in all discs of the cervical spine. In direct projection the height of the first five discs is higher in men and of the sixth - in women. The lowest height in both sexes was in the 1st intervertebral disc and the greatest – in the 4th in men and in 6th in women. Both men and women have the highest density in the 1st intervertebral disc, the lowest – in the 5th intervertebral disc. Conclusion. The height and density ratio of the intervertebral discs is different and specific for people of both genders, there is no clear correlation between them and therefore CT examination should focus on determination of the linear and qualitative parameters of the examined structures. Taking into account the frequency of the vertebral pathology among people of different age, it is advisable to include a standard checkups CT screening examination during the assessment of the cervical vertebrae for early detection of pathological changes and timely implementation of preventive or therapeutic measures.